PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS IV SD - Adittia, Arya (Universitas Pendidikan Indonesia, 2017)
The goal to be achieved in the research is to know whether the use of audio visual media can improve the learning outcomes of IPS students of grade IV SDN 2 Datar. The type of research used is quantitative research of experimental type with pre-experimental type with pre-postest design of desaign. Population used is all sample that is class IV even academic year 2016/2017 by using saturated sampling. The results showed an increase in the pretest and postest results experienced a difference. The average pretest is 65 and the posttest is 81, which means there is an increase in IPS learning outcomes of grade 4 students SDN 2 Datar after using audio visual media.Keywords: learning result, audio visual media, IPS.